Application of Data Recovery Tools in Flash Drive Forensic Data Acquisition - Muhammad Immawan Aulia; Panggah Widiandana; Latifah Iriani; Muhammad Fauzan Gustafi; Muhammad Azam Hasani (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2024)
In this fast-paced digital era, flash drives have become one of the most popular storage methods. At times, flashdrive data can be lost, and losing this data can have significant consequences both professionally and personally. In this study, an example of data recovery from an inaccessible flashdrive after being forcibly removed during the data transfer process is discussed. Static forensic methods and the Disk Drill application succeeded in finding 7626 files from unallocated partitions with a total size of 17.3 GB. The digital evidence that has been recovered is 49 files which are presented in the form of files with various extensions, such as images, audio, documents and archives. Advanced data recovery tool capabilities enable recovery of various types of files, which increases the chances of rescuing lost data.